(untitled) (CIPEEX, 2025)
This study aims to report a clinical case managed at the COE-UniEvangélica Diagnostic Clinic, with a diagnostic hypothesis of osteonecrosis associated with bisphosphonate therapy. The patient is a 78-year-old male, former smoker and alcohol user, diagnosed with multiple myeloma and undergoing treatment with zoledronic acid for the past three months. During the intraoral examination, necrotic lesions with bone exposure and purulent discharge were observed on the left mandibular alveolar ridge and on the attached gingiva bilaterally in the maxilla. The patient also presented a history of multiple dental extractions, in addition to wearing a complete maxillary denture and a removable partial mandibular denture. No facial asymmetry, swelling, or palpable lymph nodes were detected on extraoral examination. To assess the extent of bone sequestration, panoramic radiography and cone-beam computed tomography were requested, along with secretion culture and antibiogram to guide the most appropriate antibiotic therapy. Furthermore, a 0.12% chlorhexidine mouth rinse was prescribed for hygiene and pain control, and the patient was advised to discontinue denture use to avoid pressure-related complications and pathological fractures. The patient remains under follow-up while awaiting the results of all examinations to confirm the definitive diagnosis and establish the treatment plan. It can be concluded that a multidisciplinary and critical approach in the management of complex conditions affecting oncological patients.